Ethnomycology of Bracket Fungi in Baduy Tribe Indonesia - Khastini, Rida Oktorida; Wahyuni, Indria; Saraswati, Irma (Biosaintifika: Journal of Biology & Biology Education, 2018)
Inhabitants of the Kendeng mountain region depend on the biodiversity of the forest resources for their livelihood. Mushrooms are important resource that provide benefits to mankind. The aim on this research was to document traditional knowledge in bracket fungi utilization to treat health problems in Baduy tribe community. The results described in this paper were obtained through the exploration and identification of bracket fungi as well as the interview to determine their cultural significance for Baduy people. Quantitative approaches were used to determine the Use Values (UV), Informant Consensus Factor (ICF) and Fidelity level (FL) values. A total of 6 species that were identified as bracket fungi were included to Basidiomycota. The Baduy community considers the main use of bracket fungi as a medicine for several ailments. The highest UV, ICF and FL value were obtained by Ganoderma lucidum. This study provides the information regarding bracket fungi species with the high use values that could be employed in pharmacological research and further biotechnological approaches in order to achieve an adequate revenue.